Phytohormones regulate the non-redundant response of ω-3 fatty acid desaturases to low temperatures in Chorispora bungeana - Shi, Yulan; Yang, Sizhong; Zhao, Zhixing; An, Lizhe (Scientific reports, 2023)
To explore the contributions of ω-3 fatty acid desaturases (FADs) to cold stress response in a special cryophyte, Chorispora bungeana , two plastidial ω-3 desaturase genes ( CbFAD7 , CbFAD8 ) were cloned and verified in an Arabidopsis fad7fad8 mutant, before being compared with the microsomal ω-3 desaturase gene ( CbFAD3 ). Though these genes were expressed in all tested tissues of C. bungeana , CbFAD7 and CbFAD8 have the highest expression in leaves, while CbFAD3 was mostly expressed in suspension-cultured cells. Low temperatures resulted in significant increases in trienoic fatty acids (TAs), corresponding to the cooperation of CbFAD3 and CbFAD8 in cultured cells, and the coordination of CbFAD7 and CbFAD8 in leaves. Furthermore, the cold induction of CbFAD8 in the two systems were increased with decreasing temperature and independently contributed to TAs accumulation at subfreezing temperature. A series of experiments revealed that jasmonie acid and brassinosteroids participated in the cold-responsive expression of ω-3 CbFAD genes in both C. bungeana cells and leaves, while the phytohormone regulation in leaves was complex with the participation of abscisic acid and gibberellin. These results point to the hormone-regulated non-redundant contributions of ω-3 CbFADs to maintain appropriate level of TAs under low temperatures, which help C. bungeana survive in cold environments .